Analysis of lead in seaweed and waters in Bajo Island, Dompu Regency, West Nusa Tenggara - Kamula R.A.; Rijani Y.; Sambah A.B. (Biotika, 2018)
Pollutant entries, either in organic or inorganic components, result in pollution and degradation of water quality. Lead (Pb) is heavy metals having the potential to become a pollutant. This research was located in waters of Bajo Island of Saleh Bay area, Dompu Regency, West Nusa Tenggara Province. This research was conducted in July 2017 using survey method (descriptive). Determination of the sampling point coordinates used GPS. Measurement of heavy metals used AAS (Atomic Absorption Spectrophotometry) method. The results of this study showed that lead (Pb) concentrations in seawater samples from 24 sampling sites ranged from 0.26 ± 0.00 mg/kg to 0.65 ± 0.01 mg/kg which indicated that lead (Pb) concentrations in waters of Bajo Island were beyond the threshold of 0.03 mg/L (Government Regulation No. 82/2001). In addition, seaweed samples from 4 different locations showed that lead (Pb) concentrations in sample 1 ranged from 2.34 ± 0.07 mg/kg, sample 2 ranged from 1.99 ± 0.07 mg/kg, sample 3 ranged from 1.02 ± 0.06 mg/kg, and sample 4 ranged from 0.56 ± 0.08 mg/kg in which all samples showed concentrations above the standard or beyond the threshold.